Naturalization of canon law in the legislative perspective - Kroczek, Piotr (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
Currently, there is a discussion about naturalization of law, e.g. about aims, concepts, models, effects of a such phenomenon. Due to the fact, that the law of the Catholic Church is a genuine law, the discussion can be relocated into this area and the problem can be formulated in the following questions: is naturalization of canon law possible and if it is, what would it be like? The paper is a modest attempt to present the issue of naturalization in the context of canon law. First, canon law is presented as a natural phenomenon and the phenomenon which can be naturalized. Next, the examples of naturalization sensu largo and sensu stricto in canon law are demonstrated. The last part offers some guidelines and principles for the process of the naturalization of canon law. The conclusion is that naturalization must be noticed by the church legislator, but the naturalization of canon law must be done in a limited way with coherence and respect for the unique characteristics of canon law.